Fragile brain, handle with care: A case of abusive head trauma and a review of literature - Verma, Bela; Ronghe, Ashwini; Shukla, Priyanka (Indian Journal of Child Health, 2015)
We report an 11-month-old boy who brought with status epilepticus. The presence of bilateral retinal hemorrhages and generalized cerebral atrophy indicating ischemia revealed on imaging tests lead us to keep a differential diagnosis of shaken baby syndrome (SBS). On repeated questioning, mother gave the history of shaking by a relative which further supported our diagnosis. Thus in a child with a nonspecific febrile convulsive state, the treating physician should keep SBS also as a differential diagnosis.